KE ARAH INTEGRASI EKONOMI DUNIA ISLAM: STRATEGI UNTUK MENANGANI KESAN GLOBALISASI - Abd Majid, M. Shabri (Jurnal Syariah, 2019)
Globalization is a process of world nationalization. This process intends to establish a single world country under the authority of world federation government where its economic stability is controlled by world central bank. As a global and universal religion, Islam encourages its believers to act upon "together we develop" as strategy and "together we share the reward" as the ultimate aspirations in performing all daily activities, include countering the threats and gaining the advantages of globalization. Islam is not a religion of anti globalization. The concept of "ummah al-wahidah" indicates that Muslim is united by the universal concept of Islamic brotherhood. To integrate Islamic world economy, Muslim obliges to be united and co-operated to each other. The Muslim unity and co-operation have to be supported by a proper strategy to benefit the advantages and minimize the disadvantages of globalization. Confideance, trust, commitment, ethics and the way in which crises and difjiculties should be resolved among the Muslim countries is the key feature of the success towards realizing total economic integration.